COMPREHENSIVE CARE NEEDS OF POSTOPERATIVE PATIENTS IN THE RECOVERY ROOM AND RELATED FACTORS AT 115 PEOPLE'S HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To identify the comprehensive care needs of patients after general surgery in the recovery room at 115 People’s Hospital and the associated factors.Subjects and methods: A cross-sectional study was conducted on 97 postoperative general surgery patients in the recovery room of the Department of Anesthesiology and Surgical Intensive Care at 115 People’s Hospital from March to April 2025. A convenient sampling method was employed for patients who met the inclusion criteria. Data were analyzed using SPSS software, with descriptive statistics, the Chi-square test, and Fisher’s Exact test applied for statistical analysis.Results: Comprehensive care needs were identified in 15.5% of patients. Significant factors associated with these needs included type of surgery and caregiver (p < 0.05).Conclusion: The overall demand for comprehensive care among patients after general surgery in the recovery room was not high. However, postoperative general surgery patients exhibited relatively high needs in both medical and social aspects of care.
Keywords: Comprehensive care, care needs, postoperative patients, general surgery.